Investigation of the degree of social capital in Urban renewal of old textures in Zanjan old texture - Jalil Mohammadi; Alireza Mohammadi (تحقیقات کاربردی علوم جغرافیایی)
Social capital including values such as trust and cooperation and solidarity in a residential zone is a concept that has been very important and critical in the process of urban renewal in recent decades. The aim of the present study was to measure the degree of social capital and to investigate the relationship between social capital and physical interference pattern and continued motivation of residence. And it also tries to identify the type and extent of the relationship between social capital with the increased participation and the rate of the implementation of urban renewal projects, on the other hand. The present study is a survey –based research. It is descriptive - analytical. The conceptual questionnaire was used as an instrument in this study. Formulation of theoretical foundation was based on library resources. The population of the present study consisted of all the inhabitants living in Zanjan old texture (family heads) that was 46150. Using multi-stage random sampling was used and 330 samples were selected using Cochran formula. The results showed that the Zanjan old texture residents have the social capital above average; nearly it was true in all of its components. Also significance relationship does not exist between social capital and the renewal of old urban texture. Due to various factors including lack of trust in the body of urban management, lack of reinforcing the planning of required effective variables, residents are uncertain and in doubt on the issue of renewal and improvement of urban old texture. So, it emphasizes on the importance of planning in this area.